Even mildly elevated TSH is associated with an atherogenic lipid profile in postmenopausal women with subclinical hypothyroidism. (February 2015) - Geng, Houfa; Zhang, Xu; Wang, Chenggang; Zhao, Meng; Yu, Chunxiao; Zhang, Bingchang; Wang, Yong; Ban, Bo; Zhao, Jiajun
Abstract Postmenopausal women, a population with increased risk of atherosclerosis, also have an appreciable risk of subclinical hypothyroidism (SCH). The current study sought an association between serum thyrotropin (TSH), the biomarker of SCH and atherosclerosis lipid profile changes. A total of 45 postmenopausal women with SCH and 27 healthy women matched by age and body mass index were enrolled in this observational study. Serum lipid profiles and thyroid function were assessed. Compared with healthy controls, the serum levels of TC, TG, LDL-c and oxidized LDL (oxLDL) in SCH were increased by ∼22.8%, 29.6%, 30.5% and 23.2%, respectively. TSH was positively correlated with TC, LDL-c and oxLDL in all of the study subjects after adjusting for age and BMI. In particular, the positive correlation remained significant after adjusting for serum FT3 and FT4. When further stratified by TSH levels, both the subgroup of mildly elevated TSH (4.78–9.99 mU/L) and overtly elevated TSH (>10.00 mU/L) exhibited significantly higher serum levels of TC, TG, LDL-c and oxLDL compared to the normal TSH subgroup. Path analysis revealed that the total effects of TSH on TC (total effectsTC, TSH = 0.4323) included a significant direct effect (direct effectTC, TSH = 0.4932) and an indirect effect via an intermediary variable (FT3, FT4). Furthermore, TC exhibited a direct effect on LDL-c, as did LDL-c on oxLDL. In conclusion, even with a mild elevation of serum TSH, SCH is associated with atherogenic lipid profiles in postmenopausal women independent of thyroid hormones.